OTIMIZAÇÃO DAS CONDIÇÕES DO PROCESSO DE SECAGEM DO FRUTO INTEIRO E DO COPRODUTO DE ACEROLA (Malpighia emarginata DC.) EM LEITO DE ESPUMA - Paula, Krystal Cardoso Soares Estefan de (2020)
The whole fruit (WF) and by-products (BP) of the acerola (Malpighia emarginata DC.) have nutritional, technological and sensory characteristics that triggered the interest in its use by the industry. However, the high perishability of fresh fruits and the